The heuristics-and-biases inventory: An open-source tool to explore individual differences in rationality - Berthet, Vincent; de Gardelle, Vincent (Frontiers in Psychology, 2023)
Over the last two decades, there has been a growing interest in the study of individual differences in how people’s judgments and decisions deviate from normative standards. We conducted a systematic review of heuristics and biases tasks for which individual differences and their reliability were measured, which resulted in 41 biases measured over 108 studies, and suggested that reliable measures are still needed for some biases described in the literature. To encourage and facilitate future studies on heuristics and biases, we centralized the task materials in an online resource: The Heuristics-and-Biases Inventory (HBI; https://sites.google.com/view/hbiproject). We discuss how this inventory might help research to progress on major issues such as the structure of rationality (single vs. multiple factors) and how biases relate to cognitive ability, personality, and real-world outcomes. We also consider how future research should improve and expand the HBI.